Gene Cloning and Characterization of Recombinant RNase HII from a Hyperthermophilic Archaeon - Haruki, Mitsuru (American Society for Microbiology, 1998)
We have cloned the gene encoding RNase HII (RNase HII(Pk)) from the hyperthermophilic archaeon Pyrococcus kodakaraensis KOD1 by screening of a library for clones that suppressed the temperature-sensitive growth phenotype of an rnh mutant strain of Escherichia coli. This gene was expressed in an rnh mutant strain of E. coli, the recombinant enzyme was purified, and its biochemical properties were compared with those of E. coli RNases HI and HII. RNase HII(Pk) is composed of 228 amino acid residues (molecular weight, 25,799) and acts as a monomer. Its amino acid sequence showed little similarity to those of enzymes that are members of the RNase HI family of proteins but showed 40, 31, and 25% identities to those of Methanococcus jannaschii, Saccharomyces cerevisiae, and E. coli RNase HII proteins, respectively. The enzymatic activity was determined at 30°C and pH 8.0 by use of an M13 DNA-RNA hybrid as a substrate. Under these conditions, the most preferred metal ions were Co(2+) for RNase HII(Pk), Mn(2+) for E. coli RNase HII, and Mg(2+) for E. coli RNase HI. The specific activity of RNase HII(Pk) determined in the presence of the most preferred metal ion was 6.8-fold higher than that of E. coli RNase HII and 4.5-fold lower than that of E. coli RNase HI. Like E. coli RNase HI, RNase HII(Pk) and E. coli RNase HII cleave the RNA strand of an RNA-DNA hybrid endonucleolytically at the P-O3′ bond. In addition, these enzymes cleave oligomeric substrates in a similar manner. These results suggest that RNase HII(Pk) and E. coli RNases HI and HII are structurally and functionally related to one another.